CONTEXTUAL THEOLOGY IN THE DIGITAL AGE: CHALENGES AND OPPORTUNITIES FOR TEENAGERS AND YOUNG ADULTS OF THE HKBP SILALAHI CHURCH: TEOLOGI KONTEKSTUAL DI ERA DIGITAL : TANTANGAN DAN PELUANG BAGI REMAJA DAN PEMUDA GEREJA HKBP SILALAH - Dian Paulus Tambunan; Riris Johanna Siagian (Moriah Theological Seminary, 2026)
AbstractThe development of digital technology has brought significant changes in the way humans interact, communicate, and form social identities, including among teenagers and young people in the church. Amid this digital globalization, the church is challenged to reinterpret its calling contextually to remain relevant to the younger generation. This paper aims to analyze contextual theology in the digital era, specifically in the context of youth ministry at the HKBP Silalahi Church. This study uses a qualitative-descriptive approach with interviews with ten teenagers and young people of HKBP Silalahi as the primary source, complemented by a review of theological and sociological literature from books and scientific journals. The results show that digitalization opens up significant opportunities for the church to expand its ministry and deepen faith relationships through social media, creative content, and virtual spaces. However, on the other hand, challenges also arise in the form of spiritual disturbance, decreased commitment to physical worship, and a crisis of faith identity due to exposure to secular values that dominate the virtual world. Therefore, the church needs to develop a contextual theology strategy that places Christ at the center of the digital lives of teenagers and young people, through faith training, digital literacy, and a participatory ministry model. Through theological reflection and interviews, this study concludes that HKBP Silalahi's youth ministry in the digital era requires a creative and collaborative approach grounded in deep theological understanding. The HKBP Silalahi Church can serve as an example of a contextual ministry model that combines Batak faith traditions and digital innovation to foster faithfulness to the Gospel in this new era. AbstrakPerkembangan teknologi digital telah membawa perubahan signifikan dalam cara manusia berinteraksi, berkomunikasi, dan membentuk identitas sosial, termasuk di kalangan remaja dan pemuda gereja. Di tengah arus globalisasi digital ini, gereja ditantang untuk memaknai ulang tugas panggilannya secara kontekstual agar tetap relevan bagi generasi muda. Tulisan ini bertujuan untuk menganalisis teologi kontekstual di era digital, khususnya dalam konteks pelayanan remaja dan pemuda di Gereja HKBP Silalahi. Penelitian ini menggunakan pendekatan kualitatif-deskriptif dengan wawancara terhadap sepuluh remaja dan pemuda HKBP Silalahi sebagai sumber utama, dilengkapi dengan kajian literatur teologis dan sosiologis dari buku serta jurnal ilmiah. Hasil penelitian menunjukkan bahwa digitalisasi membuka peluang besar bagi gereja dalam memperluas pelayanan dan memperdalam relasi iman melalui media sosial, konten kreatif, dan ruang virtual. Namun, di sisi lain, muncul pula tantangan berupa distraksi spiritual, penurunan komitmen ibadah fisik, serta krisis identitas iman akibat paparan nilai-nilai sekular yang mendominasi dunia maya. Oleh karena itu, gereja perlu mengembangkan strategi teologi kontekstual yang menempatkan Kristus sebagai pusat kehidupan digital remaja pemuda, dengan menekankan pembinaan iman, literasi digital, dan model pelayanan yang partisipatif. Melalui refleksi teologis dan hasil wawancara, penelitian ini menyimpulkan bahwa pelayanan remaja dan pemuda HKBP Silalahi di era digital membutuhkan pendekatan yang kreatif, kolaboratif, dan berbasis pada pemahaman teologis yang mendalam. Gereja HKBP Silalahi dapat menjadi contoh model pelayanan kontekstual yang memadukan tradisi iman Batak dan inovasi digital demi mewujudkan kesetiaan kepada Injil di zaman baru ini.